Effect of tropical plant foliage on the control of methane production and in vitro ruminal protozoa population - Galindo, Juana; González, Niurca; Marrero, Yoandra; Sosa, Areadne; Ruiz, Tomás; Febles, Gustavo; Torres, Verena; Aldana, Ana I.; Achang, G.; Moreira, Onidia; Sarduy, Lucía; Noda, Aida C. (Cuban Journal of Agricultural Science, 2016)
In order to evaluate the effect of tropical plant foliage on the control of methane production and protozoa population, an experiment under in vitro conditions was carried out, where the foliage of 12 trees was used and compared to the control of Star grass (Cynodon nlemfuensis). Plants evaluated were: Leucaena leucocephala, Gliricidia sepium, Samanea saman, Albizia lebbeck, Azadirachta indica, Moringa oleifera, Pithecellobium dulce, Cordia alba, Guazuma ulmifolia, Enterolobium cyclocarpum, Tithonia diversifolia plant material (pm) 10 and Tithonia diversifolia pm 23. Methane production and protozoa population were determined. Regarding the ability of producing methane, plants were divided into four groups: (1) control, (2) plants able to reduce, at a great extent, methane production in the rumen, (3) group integrated by Enterolobium cyclocarpum, and (4) plants that can be used for reducing the ruminal methanogenesis, but at a low extent. All plants reduced the protozoa population and its populations were: 4.5; 3.7; 4.5; 4.6; 4.6; 4.5; 4, 4,6; 6; 6; 5; 6 and 9 x 106 cells.mL-1 for S. saman, A lebbeck, T. diversifolia pm 23, C. alba, L. leucocephala, P. dulce, M. oleifera, G. sepium, G. ulmifolia, T. diversifolia pm 10, E. cyclocarpum and C. nlemfuensis, respectively. It can be concluded that the evaluated plants can be used in the animal diet for reducing methane production and ruminal protozoa population.Key words: fermentation, rumen, trees, secondary metabolites